Development of a Semi-Active Bypass Viscous Damper for bridge structures subjected to dynamic loads - Farah Pour, Hengameh (2021)
Variable traffic vibration loads on overcrossing and bridges are the cause of damages in essential load-bearing components could consequently lead to damage or failure of the bridge. Nowadays, the fluid viscous dampers are the most conventional energy dissipation system to implement in bridges. However, the viscous dampers are the passive type control system and its function is the same for an entire operation time of the device. Since the applied vibration in the bridge is dependent on various traffic loads (heavy, medium, and low traffic), it is required to change the function of the damper. In this research, a Semi-active Bypass Viscous Damper is developed by utilizing a pair of external fluid flow patches as bypass valves to the sides of the viscous damper cylinder to flow the fluid from two chambers of the cylinder during the movement of the piston. Two flow control valves have been implemented in the device to control the flow pressure of the fluid passing through the bypass valve during the functioning of the damper device. Therefore, the function of the damper device is adjustable by changing the flow control valves positions within a range upon the displacement of the structure. The analytical model of the proposed bypass viscous damper is developed and the performance of the device under different loading conditions has been formulated according to the control valves position and fluid pressure inside the cylinder. Then the finite volume model of the moving fluid inside the device has been developed and the function of the device evaluated through Computational Fluid Dynamics (CFD) analysis.